Pendidikan Islam dalam Membangun Karakter Bangsa di Era Milenial - Anwar, Syaiful; salim, agus (Universitas Islam Negeri Raden Intan Lampung, 2018)
National character education aims to form a strong, competitive, moral, tolerant nation, mutual cooperation, patriotic spirit, dynamic development, knowledge and technology oriented all of which are inspired by faith and piety to the Almighty God as in aspiring to the Pancasila philosophy. Character education is an important issue in the world of education related to the phenomenon of moral decadence that occurs in the community as well as in an increasingly diverse and diverse government environment. Crime, injustice, corruption, violence against children, violation of human rights, are evidence that there has been a crisis of identity and characteristics of the Indonesian nation. The values of politeness, and religiosity that are upheld and become the culture of the Indonesian nation as long as it seems to be weak and feels foreign along with the entry of global cultural values (global culture of the era), so that it is rarely encountered in the midst of society. Islamic education is a strategic answer in realizing the formation of national character from the family (informal), institutional institutions (formal) and learning groups in the community (non-formal), which is the main capital in the formation of national character.